2013
DOI: 10.1007/s11832-013-0500-0
|View full text |Cite
|
Sign up to set email alerts
|

Review of current technologies and methods supplementing brace treatment in adolescent idiopathic scoliosis

Abstract: Purpose To report on the current technologies and methods supplementing brace treatment in adolescent idiopathic scoliosis. Methods A comprehensive literature review was performed to determine the effectiveness of bracing, to report on imaging techniques that can assist in the assessment of bracing, to understand the roles of the biomechanical treatment concepts on bracing and to address the importance of the quality of life of the brace wearers. Results The effectiveness of bracing still remains controversial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 82 publications
0
20
0
Order By: Relevance
“…It has been reported that the improved QoL flowing from in brace treatment is related to changes in pain, family relationships, and activity levels in the AIS patients. [ 31 ] A variety of surveys have been developed to evaluate the QoL in AIS patients by both scoliosis clinics and relevant service organizations, such as the Brace Questionnaire, the Bad Sobernheim Stress Questionnaire, the SRS-22 Questionnaire, and the SF-36 Survey. [ 14 , 32 ] In our study, to reduce bias and increase accuracy, we only included studies in which the QoL was assessed by SRS-22 or modified version of SRS-22 Questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the improved QoL flowing from in brace treatment is related to changes in pain, family relationships, and activity levels in the AIS patients. [ 31 ] A variety of surveys have been developed to evaluate the QoL in AIS patients by both scoliosis clinics and relevant service organizations, such as the Brace Questionnaire, the Bad Sobernheim Stress Questionnaire, the SRS-22 Questionnaire, and the SF-36 Survey. [ 14 , 32 ] In our study, to reduce bias and increase accuracy, we only included studies in which the QoL was assessed by SRS-22 or modified version of SRS-22 Questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Several literature studies [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ] have been conducted to evaluate the effectiveness of corrective orthoses. These studies mainly considered the selection of the effective brace type and predictive factors (compliance, curve magnitude, growth stage, body mass index, and exercise potential) that contribute to promising outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) and computed tomography (CT) imaging have been likewise suggested as imaging methods of the spine (Matthews and Crawford, 2006). However, these two techniques may not be very feasible, as MRI is relatively expensive, whereas CT imaging exposes adolescents to high levels of ionizing radiation (Chan et al , 2013).…”
Section: Introductionmentioning
confidence: 99%